Forensic Science, Public Trust and Criminal Justice Administration in Nigeria: A Procedural Justice Perspective - Iyamu-Ojo, Elizabeth Aiwekhoe; Imeafo, Andrew (NIU Journal of Legal Studies, 2026)
Criminal investigation and the administration of criminal justice in Nigeria are beset by systemic challenges—including poor crime scene management, pervasive reliance on confessional statements extracted under duress, and a conspicuous absence of forensic science capacity—which collectively erode public trust in law enforcement institutions and undermine the legitimacy of the criminal justice system. This article examines the intersection of forensic science, public trust, and criminal justice administration in Nigeria through the analytical lens of procedural justice theory. Adopting a doctrinal and socio-legal methodology, the article draws on a wide body of literature spanning forensic science, criminology, and public law, alongside Nigerian legislation—most notably the Administration of Criminal Justice Act 2015—and comparative jurisprudence from the United Kingdom, United States, and South Africa. The article argues that the deployment of reliable forensic science not only enhances the truth-finding function of the criminal justice system but also serves as a structural mechanism for building institutional legitimacy and public trust, consistent with the demands of procedural justice theory as advanced by Tyler, Jackson, Bradford and Hough. By demonstrating that scientific investigations reduce bias, minimise wrongful convictions, and improve the transparency of criminal proceedings, the article shows that forensic science operationalises the core values of procedural justice such as fairness, neutrality, voice, and dignity. The article further identifies the principal challenges confronting the effective deployment of forensic science in Nigeria, including underfunded laboratories, inadequate training, weak evidential standards, and institutional corruption. Drawing on comparative models and international best practice, the article advances specific recommendations for a national forensic science policy, accreditation of laboratories, judicial education, investment in digital forensic capacity, and community engagement. It concludes that strengthening forensic science infrastructure in Nigeria is not merely a technical imperative but a democratic one: a precondition for a criminal justice system that commands the confidence and voluntary compliance of the citizenry. Keywords: Forensic Science, Criminal Investigation, Public Trust, Procedural Justice, Legitimacy, Nigeria, Criminal Justice Administration, Wrongful Convictions, DNA Evidence, Digital Forensics.